Effects of transverse reinforcement spacing on the response of reinforced concrete columns subjected to blast loading. (1st July 2017) - Kyei, Conrad; Braimah, Abass
Highlights: Three column types were modelled using LS-DYNA code. The columns are detailed according to CSA A23.3 for nonseismic and seismic response. The numerical models were validated with live explosion testing conducted by others. Seismic detailing increases blast-resistance of RC columns at low scaled distances. Seismic detailing has negligible effect on blast-resistance at high scaled distances. Abstract: Concerns have risen from building responses and resulting fatalities in some recent infamous terrorist attacks. The collapse of the Alfred P. Murrah Building, for instance, revealed that failure of load-bearing members could lead to extensive building failure. It has become imperative to investigate the blast resistance offered by loading-bearing structural members designed for gravity loads and other load types such as earthquakes. Reinforced concrete (RC) columns not forming part of the seismic force resisting system were detailed according to CSA A23.3-04 – Design of Concrete Structures. Using a high-fidelity physics-based finite element code, LS-DYNA, a numerical study was undertaken to investigate the effects of transverse reinforcement spacing on the blast resistance of RC columns. The study shows that the effect of transverse reinforcement spacing and axial loading significantly affects RC column behaviour under blast loading at low scaled distances. At higher scaled distances, however, the effects were insignificant.